EP1228 LIBUSE trial – algorithm for cervical cancer screening in the czech republic with usage of HPV DNA testing with HPV 16/18 genotyping and p16/Ki-67 dual-stained cytology. (1st November 2019) - Slama, J; Dvorak, V; Trnkova, M; Skrivanek, A; Novackova, O; Ovesna, P
Abstract : Introduction/Background: The incidence of cervical cancer in the Czech Republic remains stable over more than 30 years irrespective of existing national screening based on annual collecting of Pap smears. The aim of our prospective trial was to evaluate the role of HPV DNA testing with 16/18 genotyping and triage with p16/Ki-67 immunocytochemistry. Methodology: Women between 30 and 60 years who had in 12 collaborating centres regular annual Pap smear were co-tested for HPV DNA with selective 16/18 genotyping (Cobas 4800, Roche). All HPV 16/18 positive cases and/or those with severe abnormality in cytology were directly refered for colposcopy; HPV non-16/18 positive cases and LSILs were triaged using p16/Ki-67 dual-stained cytology (CINtec Plus, Roche) and positive cases were refered for colposcopy while negative cases were further followed. Results: Altogether 2407 patiens were eligible for analysis after first round of screening. Mean age of subjects was 43 years. Pap smears showed 8 cases with severe and 105 cases with mild abnormalities. There were 7.4% (180/2418) patients with HPV positivity, from which 50 had HPV 16 and/or 18. Biopsy confirmed 32 high-grade squamous and 2 glandular lesions, all of them were HPV positive. Triage using p16/Ki-67 was positive in 22.5% cases (29/129). Conclusion: Screening based on HPV testing with selective 16/18 genotyping and p16/Ki-67 triage found during the first round four times more high-grade lesions including glandular lesions than standard screening based on Pap smears. Disclosure: Nothing to disclose.